2020
DOI: 10.12765/cpos-2020-04
|View full text |Cite
|
Sign up to set email alerts
|

Remittance Behaviour of Intra-EU Migrants – Evidence from Hungary

Abstract: After the eastern expansion of the European Union (EU), a large number of emigrants left their home countries to work in economically better developed western member states. Hungary followed this EU emigration trend with a certain time lag. However, the rising number of emigrants caused structural problems in the domestic labour market. A comprehensive examination of intra-EU remittances as one of the major determinants of migration has been outside the scope of recent research activity. The data from the Hung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They performed the analysis in the period 2000-2018 searching for the impact of remittances on the GDP per capita and GDP per capita growth, where the results show a positive impact on GDP per capita, while their impact on GDP per capita growth was not found. Kajdi and Ligeti (2020) studied the remittances in Hungary with two intentions: to provide empirical evidence for the major factors that determine the remittance propensity (probit regressions) and to introduce variables that are associated with money transfer (OLS regressions). Their approach is based on the characteristics of the senders and they found that older men with vocational school education have the highest remittance propensity, and the likelihood of sending private support is higher among short-term migrants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They performed the analysis in the period 2000-2018 searching for the impact of remittances on the GDP per capita and GDP per capita growth, where the results show a positive impact on GDP per capita, while their impact on GDP per capita growth was not found. Kajdi and Ligeti (2020) studied the remittances in Hungary with two intentions: to provide empirical evidence for the major factors that determine the remittance propensity (probit regressions) and to introduce variables that are associated with money transfer (OLS regressions). Their approach is based on the characteristics of the senders and they found that older men with vocational school education have the highest remittance propensity, and the likelihood of sending private support is higher among short-term migrants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many high-skilled migrants from the CEE cause structural problems in the domestic labor market. It exists in the health care in the CR, or in Hungary from where emigrants go to the West for altruistic motives to support the household who remain behind [17].…”
Section: A Theoretical Ground Of the Career Developmentmentioning
confidence: 99%